Materials, Use, Buying, and Selling Eyelash Extensions from Sharia Economic Law Perspective - Seli Selviani; Hasan Bisri; Heris Suhendar (Mabahits Al-Uqud, 2024)
Eyelash extensions are false eyelashes that are widely used by women today. Eyelash extensions are sold freely without having halal certification and permission from BPOM. According to Fiqh al-bai, this study aimed to discover the halalness of eyelash extension products and the law of buying and selling eyelash extensions. This research uses a descriptive-analytical method. Based on research results, the material for making eyelash extensions is usually made from human hair and keratin. In addition, using eyelash extensions can cause ablution and make obligatory bathing invalid because water cannot be used directly to touch the skin. The law of buying and selling eyelash extensions, according to Fiqh al-Ba'i, is not permissible because it does not meet the requirements for the object of sale and purchase. Namely, the goods being traded are neither halal nor holy